'There's a new sheriff in town': the Rodchenkov Act, anti-dopism, and the hegemony of WADA in international sport. Issue 6 (23rd May 2022) - Henning, April; Andreasson, Jesper
Abstract: The World Anti-Doping Agency (WADA) has long been the organization responsible for making and harmonizing anti-doping policies in international sport. As the Rodchenkov Act was signed into law in the United States, however, it became possible for the U.S. to target organizers of systematic doping with criminal penalties even outside their national borders, and in doing so also pose a challenge to WADA's hegemony over the anti-doping narrative. Drawing on official organizational statements and those made by sport stakeholders in media coverage, this article uses the implementation of the Rodchenkov Act as a case study to dissect and analyze the interdependence between national and international anti-doping policy/laws. The analysis shows how the U.S., through the Rodchenkov Act, is pushing the accepted anti-doping paradigm to an extreme and engaging in a form of resistance against WADA's hegemony. By extending its own authority and abilities beyond its national borders and applying tougher sanctions on doping conspirators, the U.S./USADA position themselves as being the party strong enough to lead and shape the anti-doping regime. In effect, they are grabbing power from WADA and dislocating its hegemony in the process. Even as it reordered its national values above global sport values, it was able to leverage anti-dopism in service of its own goals of authority.